“El Buscapié” o el casticismo de Montalvo (Dossier Seis miradas al cuerpo y al deseo de una poética latinoamericana desde hace cinco siglos) - Galván, José Luis (2017)
The ideal of the language of Cervantes tries to overcome the particular objective realism of his time, the Renaissance, and to print his own mark: the multidimensionality of language. Not only do they consist of his remonstrances to Sancho as mere grammatical formulas; they seek a more complete and complex solution to Renaissance rationality. Montalvo, in his search for the unity of the language, does not skimp on the rejection of popular speech, its precariousness and lack of plasticity. The model will be Spain, but that of good writers. “El Buscapié,” a prologue to Capítulos que se le olvidaron a Cervantes, is particularly important to observe his passionate defense of the Spanish in Spain: the Academy, academics and writers of El Siglo de Oro.